A3_1 Falling With Style - Yeo, Adam; Routledge, Hannah; Lewis, Jacob; Meggi, Dikshita (Physics Special Topics, 2021)
In 2010, a paper concluded that Buzz Lightyear could take flight at an optimum flight angle of 13◦ if he was provided with 62 N of thrust and was travelling at 55 m/s [1]. In this paper we analyse how fast Buzz would need to be travelling to generate enough lift for flight while at an attack angle of 0◦ , as seen in the films. By making the large assumption that Buzz’s wings are similar to those of a cambered airfoil, we calculated that Buzz can generate enough lift to fly with a 10 inch firework by reaching 66.310 m/s ± 1.500 m/s ."